2017
DOI: 10.1016/j.seizure.2017.07.009
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital outcomes and delayed neurologic sequelae of seizure-related endosulfan poisoning

Abstract: Seizure-related endosulfan poisoning had higher progression rates to SE and RSE and higher fatality rates than other drug-induced seizures. However, delayed neurologic sequelae after discharge were not demonstrated. Due to the high progression rates from seizure-related endosulfan poisoning to SE and RSE and the absence of an established treatment for SE-related endosulfan poisoning, physicians should aggressively treat patients who experience a seizure after endosulfan poisoning and who present with decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…However, endosulfan poisoning still occurs due to stocks of endosulfan that existed prior to the implementation of the prohibition. One study reported admitting six cases of acute endosulfan poisoning in a single hospital between 2014 and 2016 4. In the present case, acute poisoning by endosulfan occurred in May 2017, implicating that clinicians should focus on the management of endosulfan intoxication even if it was phased out in the market.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…However, endosulfan poisoning still occurs due to stocks of endosulfan that existed prior to the implementation of the prohibition. One study reported admitting six cases of acute endosulfan poisoning in a single hospital between 2014 and 2016 4. In the present case, acute poisoning by endosulfan occurred in May 2017, implicating that clinicians should focus on the management of endosulfan intoxication even if it was phased out in the market.…”
Section: Discussionmentioning
confidence: 67%
“…The patient was subjected to 9-day coma therapy and 2-month AED treatment. A recent study reported that the progression rates of endosulfan poisoning-related seizures to SE and RSE were 78.1% and 54.4%, respectively,4 considerably higher than that of other drug-induced seizures, reported to reach 10% 9. This could be attributed to the high lipid solubility of endosulfan; despite its short half-life in the plasma, endosulfan is rapidly absorbed, quickly reaches tissues such as the CNS, and then is slowly released from its lipophilic depots 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…by chlorinated pesticides and convulsions were observed in mice (Cole and Casida 1986), whereas poisoning with the organochlorine insecticide endosulfan caused seizure, status epilepticus, or refractory status epilepticus in humans (Durukan et al 2009;Moon et al 2017;Moses and Peter 2010;Parbhu et al 2009;Roberts et al 2004), and eventually led to the death of a farmer (Roberts et al 2004) and a toddler (Parbhu et al 2009).…”
Section: Endosulfanmentioning
confidence: 99%